Immunoglobulin G4-related immune responses to common food antigens in patients with ulcerative colitis and Crohn’s disease - Hong Sub Lee; Kwang Jae Lee (Turkish Journal of Gastroenterology, 2019)
Background/Aims: It is unclear whether IgG4-related immune responses to food can play a role in the pathogenesis of inflammatory bowel disease (IBD). The aim of the present study was to investigate the serum levels of IgG4 to common food antigens in patients with ulcerative colitis (UC), Crohn’s disease (CD), and healthy controls. Materials and Methods: Thirty-six patients with CD (n=12) or UC (n=24) and 36 sex- and age-matched healthy individuals (mean age, 49 years) participated in the study. Serum levels of IgG4 to 90 common food antigens were measured. The number of subjects with positivity, defined by cut-off values ≥0.7 U/mL, was compared. Results: Serum titers of IgG4 to salmon, onion, shrimp, cuttlefish, eel, millet, gluten, soybean, and coconut in patients with IBD were significantly or tended to be higher than those in the control group. Serum levels of IgG4 to salmon, millet, and onion in patients with CD were significantly or tended to be higher than those in the control group. Serum titers of IgG4 to cuttlefish and onion in patients with UC tended to be higher than those in the control group. The number of subjects with positivity to cod, tuna, mackerel, oat, pea, peanut, and coconut was significantly higher in patients with CD than in healthy controls. The number of subjects with positivity to kiwi and cuttlefish was significantly higher in patients with UC than in controls. Conclusion: Patients with IBD shows higher serum levels of IgG4 to diverse food antigens. Patients with CD present IgG4-related immune reactions to more foods than patients with UC. Cite this article as: Lee HS, Lee KJ. Immunoglobulin G4-related immune responses to common food antigens in patients with ulcerative colitis and Crohn’s disease. Turk J Gastroenterol 2019; 30(5): 408-14.